RECORD ON SOME CATERPILLARS OF BUTTERFLIES (LEPIDOPTERA: PAPILIONOIDEA) IN EAST JAVA, INDONESIA - Abdul M. Shahroni; Fariq I. A. Shidiq; Soenarko Soenarko; Lutfi Irwansyah; Djunijanti Peggie (TREUBIA, 2022)
Indonesia has a high diversity of butterflies with more than 2,000 species, yet knowledge of their pre-adult stages is very limited. A thorough understanding of the larval stage is necessary to complement the data on butterfly diversity and distribution. This survey, which lasted from 2012 to 2022, aimed to document the butterfly larvae in their last instars that were encountered in East Java. Leaves of the host plants were visually inspected during the day to collect butterfly eggs or larvae. The eggs and larvae were then reared to adulthood and resulted in 136 verified species in total. Of 136 species, the caterpillars of 107 species (78.68%) had previously been documented, and those of 29 species (21.32%) are newly reported here, including the caterpillars of Eurema beatrix and Ixias venilia, which are rare and endemic to Java. This information will serve as a substantial part of developing a field guide to the butterflies of Java, which will include pre-adult stages.